Molybdenum Nitride Nanocatalyst Derived from Melamine and Polyoxometalate‐based Hybrid for Oxidative Coupling of Amines to Imines with Air. Issue 19 (22nd August 2018) - Li, Yue; Xiao, Kang; Li, Jingjing; Jiang, Pingping; Jiang, Yuchen; Du, Shengyu; Leng, Yan
Abstract: Molybdenum nitride (Mo2 N) is one of the most promising alternative catalysts for a wide range of Pt‐catalyzed catalytic applications but is seldom investigated in oxidative coupling of amines to imines. A Mo2 N‐based nanocatalyst is successfully achieved by the hybridization of PMo12 O40 3− (PMo)‐paired ionic pyridine‐4‐carboxylic acid (PC) and melamine (Mel), followed by calcination in N2 . Melamine acts as an outstanding carburization and nitridation reagent that can convert into carbon nitride, and meanwhile the released N element react with Mo species in PMo to form Mo2 N. The obtained catalyst PC‐PMo‐Mel‐800 exhibits high activity and remarkable stability for the oxidative coupling of amines to imines under solvent‐free and atmospheric conditions. This is the first case of Mo2 N‐catalyzed oxidative coupling reaction catalyst. The strategy reported herein for fabricating Mo2 N may provide a significant and interesting approach to design more transition metal nitrides for wide catalytic applications. Abstract : Rarely studied : A Mo2 N‐based nanocatalyst prepared by calcination of melamine and PMo12 O40 3− (PMo)‐based ionic hybrid was demonstrated to be a highly active and stable heterogeneous catalyst for the oxidative coupling of amines to imines under solvent‐free and atmospheric conditions. The strategy in this work may provide a facile way to fabricate more stable transition‐metal nitrides with desired performance for more practical catalytic applications.